Campur Kode Pada Komunikasi Promosi Dalam Iklan Penawaran Jasa Di Internet - Kurniawan, Eko; , Prof. Abdul Ngalim; , Prof. Markhamah (2016)
The purpose of this study was to describe the form and function of the use of code-mixing, the relationship between the forms of code-mixing with things that are promoted, as well as the relationship between the image or appearance in the ad offers services on the internet. This research uses descriptive qualitative research. Based on data analysis, obtained a description of the use of code-mixing in the form of words, phrases, form baster, repetition of words and expressions or idioms. By looking at the emergence of code-mixing intensity data, code-mixing 31 tangible word, phrase intangibles 30 code-mixing, code-mixing intangible clause 1, 1 code-mixing tangible expressions or idioms and one form of code-mixing in the form Baster. Retrieved function of the relationship between forms of code-mixing with things that are promoted, (1) Mix the code as a confirmation of the product and services that offer in the advertisement, (2) Mixed code to facilitate the delivery of intent in advertising service offerings, (3) Mixed code were facilities or means of service offerings, (4) Mixed code as a form of service or product and services offered. And the relationship between the image or appearance in the ad as (1) Draw a tool facilities used in service (2) Images of the form of the services of the products offered (3) Figure in the form of how the implementation of the services and attractions offered (4) Figure form activities of the activities offered services.